Behaviour of reinforced concrete beam with circular opening using different fraction volume of hybrid fibre - Norarina, Noran (2018)
Reinforced concrete beams with opening commonly used to facilitate essential services such as water supply pipes, drainage pipes, air conditioning electricity, telephone lines and computer network lines. The experimental work presented in this research is aimed to investigate experimentally the behaviour of beams with circular opening at the end of span. The research also conducted to study the potential of hybrid fibre in strengthening reinforced concrete beam using different fraction volume. The combination of steel fibre and kenaf fibre were used in this study. The study was carried out by casting beam with the addition of 0% hybrid fibre, 1% hybrid fibre and 2% hybrid fibre on the mixture of reinforced concrete beam. 18 cubes of all sides equal to 150 mm and 4 beams of dimensional 400x250x1200 mm were casted. All cubes specimens was tested until failure in compression machine. The beams were casted for 28 days and undergo flexural test. All the samples were tested and results were analysed using Microsoft Excel and presented with the aid of tables and graph. The study shows that, the reinforced concrete beam with the addition of hybrid fibre can sustain more than 200kN of load. However, the addition of hybrid fibre in concrete mix showed insignificant effect in compressive strength. Reinforced concrete beam with hybrid fibre show better performance as there is no excessive cracking until the structure had failed. Mode of failure of the beam changed from brittle to a more ductile manner as the amount of steel fibres was increased in the concrete mix. In term of ductility, the ductility is enhanced as 1% hybrid fibre was added but there is a limit exist which additional fibres lead to less ductile.